Diffusion of Cardiopulmonary Resuscitation Training to Chinese Immigrants with Limited English Proficiency - Yip, Mei Po; Ong, Brandon; Tu, Shin Ping; Chavez, Devora; Ike, Brooke; Painter, Ian; Lam, Ida; Bradley, Steven M.; Coronado, Gloria D.; Meischke, Hendrika W. (Emergency Medicine International, 2011)
Cardiopulmonary resuscitation (CPR) is an effective intervention for prehospital cardiac arrest. Despite all available training opportunities for CPR, disparities exist in participation in CPR training, CPR knowledge, and receipt of bystander CPR for certain ethnic groups. We conducted five focus groups with Chinese immigrants who self-reported limited English proficiency (LEP). A bilingual facilitator conducted all the sessions. All discussions were taped, recorded, translated, and transcribed. Transcripts were analyzed by content analysis guided by the theory of diffusion. The majority of participants did not know of CPR and did not know where to get trained. Complexity of CPR procedure, advantages of calling 9-1-1, lack of confidence, and possible liability discourage LEP individuals to learn CPR. LEP individuals welcome simplified Hands-Only CPR and are willing to perform CPR with instruction from 9-1-1 operators. Expanding the current training to include Hands-Only CPR and dispatcher-assisted CPR may motivate Chinese LEP individuals to get trained for CPR.